Diet and physical activity behavior among users of prescription weight loss medications - Serdula Mary K; Khan Laura; Blanck Heidi (BMC, 2004)
Abstract Background There is limited population-based data on diet and physical activity behaviors and weight loss among users of prescription weight loss medications. Most findings are from clinical settings or from research that includes organized behavioral programs. Methods We analyzed data from the 1998 Behavioral Risk Factor Surveillance System, an annual telephone survey conducted in all fifty states, the District of Columbia and Puerto Rico. The sample consisted of 135,435 noninstitutionalized adults aged 18 years old and older. We determined the prevalence and odds of prescription weight loss medication use, odds of 10% weight loss, and among current weight loss medication users, the prevalence and odds for diet and physical activity behaviors. Results 10.2% of obese women and 3.1% of obese men reported using prescription weight loss medications in the past 2 years. Of users, 28.2% had lost at least 10% of their pretreatment body weight. The odds of losing at least this much weight were higher among women, those who usually consumed ≥ 5 fruits and vegetables daily and those who met physical activity recommendations. Among current prescription weight loss medication users, 26.7% reported both eating fewer calories and meeting recommended leisure-time physical activity levels (<40% of any group met both). Of those meeting both recommendations, almost half (47.2%) had lost 10% of their pretreatment body weight. Of current users, 9% reported using the medications for weight maintenance. Conclusions Only 26.7% of prescription weight loss medication users reported following recommended diet and physical activity behaviors. Further research is needed to assess whether behavioral changes are associated with greater weight loss and maintenance among prescription weight loss medication users.